Enhanced bioethanol production using atmospheric cold plasma-assisted detoxification of sugarcane bagasse hydrolysate. (October 2020) - Lin, Shin-Ping; Kuo, Tai-Ching; Wang, Hsueh-Ting; Ting, Yuwen; Hsieh, Chang-Wei; Chen, Yu-Kuo; Hsu, Hsien-Yi; Cheng, Kuan-Chen
Graphical abstract: Highlight: The effects of toxic compounds in bioethanol production were evaluated. ACP provides great degradation rate for formic acid (31%) and acetic acid (45%). ACP exhibits excellent degradation rate for HMF (80%) and furfural (100%). ACP treated SCBH as alternative carbon source can enhance bioethanol production. The detoxified SCBH with nitrogen substitute in bioethanol production was studied. Abstract: The current study used acid hydrolysis of lignocellulosic materials to obtain fermentable sugar for bioethanol production. However, toxic compounds that inhibit fermentation are also produced during the process, which reduces the bioethanol productivity. In this study, atmospheric cold plasma (ACP) was adopted to degrade the toxic compounds within sulfuric acid-hydrolyzed sugarcane bagasse. After ACP treatment, significant decreases in toxic compounds (31% of the formic acid, 45% of the acetic acid, 80% of the hydroxymethylfurfural, and 100% of the furfural) were observed. The toxicity of the hydrolysate was low enough for bioethanol production using Kluyveromyces marxianus . After adopting optimal ACP conditions (200 W power for 25 min), the bioethanol productivity improved from 0.25 to 0.65 g/L/h, which means that ACP could effectively degrade toxic compounds within the hydrolysate, thereby enhancing bioethanol production. Various nitrogen substitute was coordinated with detoxified hydrolysate, and chicken meal group presented the highest bioethanol productivity (0.45 g/L/h).